The Impact of Economic Growth and Unemployment Rate on Poverty in Sulawesi - Roflan R Badu; Syarwani Canon; Fitri Hadi Yulia Akib (Gorontalo State University, 2020)
This research aims to analyze several fators that may impact the provincial poverty rate in Sulawesi. Several factors considered in this research is the economic growth (growth of Gross Regional Domestic Product) and Unemployment Rate. This research uses secondary data from Central Statistics Bureau (Badan Pusat Statistik, BPS). This research uses panel data analysis on six provinces in Sulawesi during 2010-2017. This research uses Fixed Effect Model (FEM). Based on the results, it is found that economic growth and unemployment rate has significant and positive impact on poverty rate in Sulawesi. Keywords: Economic Growth; Unemployment Rate; Poverty.